Employer Size and Dual Labor Markets - Rebitzer, James B.; Robinson, Michael D. (The Review of Economics and Statistics, 1991)
Recently developed effort regulation models argue that labor markets are segmented because of differences in the technology of supervision across firms. primary jobs pay above market clearing wages because these jobs are difficult to monitor. Secondary jobs, in contrast, pose no monitoring difficulties and therefore pay a market clearing wage. If, as the literature suggests, increases in employer size make supervision more difficult, we should observe that wages increase with employer size in primary jobs but not in secondary jobs. We test this hypothesis using a switching regression model. We find evidence of an employer size wage effect in both primary and secondary labor markets. However, consistent with the prediction of effort control models, the size effect on wages is considerably larger in primary than secondary jobs.